Against all odds: successful maternal outcome after massive abruption with intrauterine fetal demise and severe coagulopathy - Joshi, Surbhi; Gupta, Manisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
A 31-year-old multiparous woman presented with antepartum hemorrhage and intrauterine fetal demise (IUFD), who developed severe DIC (INR 6.0) and acute kidney injury (AKI). Despite multi-organ involvement, the patient made a complete recovery. Early multidisciplinary intervention and aggressive supportive management were the key to survival.